Developing the Animation Video to Increase Vocabulary Learning Achievement among Students in the Fifth Grade of Nahdlatul Ulama 56 Islamic Elementary School Krajankulon Kaliwungu Kendal - Nafiah Nafiah; Fikrotul Khusnia (Gunung Djati Conference Series, 2023)
Arabic language study, especially vocabulary learning in Islamic Elementary School 56 Nahdlatul Ulama Krajankulon Kaliwungu Kendal was conducted with less diverse methods and mediums in the classroom, so students feel bored and considered Arabic a difficult subject. There was a need for educational aids in the form of video animation in Arabic material to reduce these problems. The objectives of this research were to develop animation videos to assimilate Arabic vocabulary learning using the ADDIE development model of R&D consisting of; Need Analyze, Design, Development, Implementation, and Evaluation. The R&D results of this research were based on the five stages, First, the results of needs analysis through student questionnaires on Arabic language education obtained 63% of 28 students met the need criteria. Second, designing products by preparing competency maps, material maps, and manuscripts. Third, the development of video animation media and the expert validation test, i.e. the material expert gets an 85% realization rate and the media expert gets an achievement rate of 90%. Fourth, an application of the animation video product to 28 students of class 5A. As for the application of the video animation product, a pretest was conducted, then a product trial, a dimensional test, and an attractiveness test were conducted for the video animation product, which results in a score of 85% with very attractive criteria. Fifth, an evaluation of the video was done and said to be effective to increase vocabulary learning achievement.